(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article discusses indirect methods based on various physical properties of materials. The most common conductometric, based on the resistivity of cotton samples, dielectric based on the dielectric properties of cotton, with a change in humidity, the electrical capacitance of the sensor with the sample changes, which is recorded by a secondary device and the humidity is determined using a special scale. But these methods, along with the simplicity of design and speed of operation, are unsuitable for cotton materials in mutual settlements due to the large measurement error (more than 0.5% abs at humidity up to 10% and more than 5.0% relative at humidity more than 10%), but they can be used to control technological processes of drying, cleaning and moistening of raw cotton and fiber.